Water Availability Pattern and Water Requirement of Kharif Crops in Saurashtra Region, Gujarat - Sahu, D D; Sastry, P S.N (Annals of Arid Zone, 2016)
Climatic water balance on weekly basis for individual years in respect of three main agricultural research stations in Saurashtra region was evaluated and periods of water deficits and soil moisture recharge were worked out. Aridity index with reference to crop phenophases was determined and the reference crop Er. water requircmcnt. water requirement satisfaction index (WRSI) in each of the phenophases for the important Kharif naps, pearlmillet (Pennisetum typhoides). sorghum (sorghum ,vulgare). Groundnut (Arachis hypogae) and cotton (Gossypium hirsurn) arc evaluated. In general. analyis showed that the Junagadh has large surplus while the Jamnagar and Rajkot showed mid-seasonal moisture deficit with no watersurplus during any week in the growing season, In case of Junagadh for the four crops studied. the coefficient of variation in water requirements at individual growth stages of crops are also discussed,